(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
When a contact or near contact shot is fired from a rifled firearm, apart from the muzzle imprint other constructional parts like front sight and/or the recoil spring guide of semiautomatic pistols may surround the bullet entry wound. But when a rifle fitted with a flash suppressor is fired, the emerging soot-laden gas in the barrel escapes from the slits of the flash suppressor. If the shot is contact or near contact, the flash suppressor will produce a characteristic “flower-like” pattern of blackened zones around the entrance, or rarely may produce deep burns mimicking “grouping of gun-shot entry wounds”. We present a case where due to deep dermal burns resulting from escaping hot soot-laden gases through the slits/ openings of a flash suppressor of an infantry rifle in a contact shot mimicked multiple entry wounds.